Disaster response under One Health in the aftermath of Nepal earthquake, 2015. Issue 1 (March 2017) - Asokan, G.V.; Vanitha, A.
Abstract: Until now, an estimate quotes that 1100 healthcare facilities were damaged and over 100, 000 livestock lost in the two earthquakes that occurred in April and May of 2015 in Nepal. Threats of infectious diseases, mostly zoonoses, could affect Nepal's economy, trade, and tourism, and reaching the targets of the United Nations Millennium Development Goals. Historically, outbreaks of infectious diseases, including zoonoses, were largely associated with the aftereffects of the earthquakes. It has been documented that zoonoses constitute 61% of all known infectious diseases. Therefore, the purpose of this communication was to examine the infectious disease outbreaks after earthquakes around the world and explore the risk assessment of the zoonoses threats reported in Nepal and highlight adopting One Health. Our summaries on reported zoonoses in Nepal have shown that parasitic zoonoses were predominant, but other infectious disease outbreaks can occur. The fragile public health infrastructure and inadequately trained public health personnel can accelerate the transmission of infections, mostly zoonoses, in the post impact phase of the earthquake in Nepal. Therefore, we believe that with the support of aid agencies, veterinarians and health professionals can team up to resolve the crisis under One Health.